2017
DOI: 10.3389/fmicb.2017.00760
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sea Actinomycetes and Their Secondary Metabolites

Abstract: Deep sea is a unique and extreme environment. It is a hot spot for hunting marine actinomycetes resources and secondary metabolites. The novel deep sea actinomycete species reported from 2006 to 2016 including 21 species under 13 genera with the maximum number from Microbacterium, followed by Dermacoccus, Streptomyces and Verrucosispora, and one novel species for the other 9 genera. Eight genera of actinomycetes were reported to produce secondary metabolites, among which Streptomyces is the richest producer. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 86 publications
2
83
0
1
Order By: Relevance
“…200-500 m depth and which were once regarded as being biologically inert (Forbes' azoic theory [14]), a notion that was dispelled in the late nineteenth century. Abundant life and biodiversity is now welldocumented even at abyssal (>2 000 m) and hadal (>6 000 m) depths and actinobacteria have been isolated from sediments taken at all of these extremes [8,[15][16][17][18]. Conditions found in these oceans include high pressure, temperature and salinity extremes, low nutrient status and anoxia.…”
Section: Bioprospecting Biomes and Sitesmentioning
confidence: 99%
“…200-500 m depth and which were once regarded as being biologically inert (Forbes' azoic theory [14]), a notion that was dispelled in the late nineteenth century. Abundant life and biodiversity is now welldocumented even at abyssal (>2 000 m) and hadal (>6 000 m) depths and actinobacteria have been isolated from sediments taken at all of these extremes [8,[15][16][17][18]. Conditions found in these oceans include high pressure, temperature and salinity extremes, low nutrient status and anoxia.…”
Section: Bioprospecting Biomes and Sitesmentioning
confidence: 99%
“…Marine bacteria belonging to Actinobacteria are well documented in the aspect of antibiotics or secondary metabolite producers (e.g., Blunt et al, 2013;Abdelmohsen et al, 2014;Kamjam et al, 2017). In this study, Actinobacteria was found to be the predominant phyla with 18.0% in healthy corals whereas its abundance severely affected in the SGA corals with just 6.4%.…”
Section: Resultsmentioning
confidence: 59%
“…Marine natural products show higher incidences of significant bioactivity and chemical novelty when compared with compounds from terrestrial microorganisms. Therefore, marine organisms that can survive in extremes of pressure, salinity and temperature may be important untapped resources of structurally diverse and biologically active secondary metabolites [1,2]. In order to find new sources of novel bioactive compounds, we isolated actinomycete strains from deep-sea sediment samples.…”
mentioning
confidence: 99%